Large Cell Neuroendocrine Cancer (LCNEC) of Uterine Cervix - Baral, Gehanath; Sharma, Reetu (Ibrahim Medical College Journal, 2009)
A rare type of cervical cancer was encountered as a neuroendocrine cancer of cervix. Clinically, the patient presented with bleeding per vagina. She refused biopsy in her first visit and did not come for follow up. However, after few months she came and since there was a polypoid growth from cervix, she was advised to undergo hysterectomy. Histopathologically, it was diagnosed as large cell type of neuroendocrine cancer. Multimodality systemic treatment was offered as per literature. Ibrahim Med. Coll. J. 2009; 3(1): 36-38 Key words: Uterine cervix, neuroendocrine cancer (NEC), human papilloma virus (HPV) doi: 10.3329/imcj.v3i1.2919